Pengaruh Bawang Putih Tunggal (Allium Sativum L) pada Aterosklerosis - Angie Carolyn; agustyas tjiptaningrum; anggraini janar wulan (Medula, 2021)
Atherosclerosis is characterized by changes in the size of arteries caused by the formation of atherosclerosis plaques consisting of necrosis cells, calcified areas, modified lipid accumulation, smooth muscle cells, endothelial cells, leukocytes, and foam cells. Coronary Artery Disease and stroke are the main clinical manifestations of atherosclerosis. One of the causes of aeroskelrosis is consuming too much food that contains high fat. The interaction between oxidized LDL and the walls of blood vessels, can cause endothelium dysfunction. In addition, oxidized LDL stimulates the formation of lipid peroxide free radicals, makes mononuclear cells (monocytes) differentiate into macrophages, then begins inflammation by removing pro-inflammatory cytokines. Single Clove Garlic (SGC) is a tropical plant found in Indonesia and is often used as an herbal remedy. Single Clove Garlic is a variation of garlic that is formed accidentally, due to extreme conditions. This type of onion contains Alliin (411.4 mg/mL), Allicin (268.2 mg/mL) and ajoene which makes it have a higher antioxidant capacity than regular garlic.  The use of SGC as quoted is considered to be beneficial for the cardiovascular system.